The Intestinal Microbiota and Metabolites in the Gut-Kidney-Heart Axis of Chronic Kidney Disease - Huang, Yinghui; Xin, Wang; Xiong, Jiachuan; Yao, Mengying; Zhang, Bo; Zhao, Jinghong (Frontiers in Pharmacology, 2022)
Emerging evidences demonstrate the involvement of gut microbiota in the progression of chronic kidney disease (CKD) and CKD-associated complications including cardiovascular disease (CVD) and intestinal dysfunction. In this review, we discuss the interactions between the gut, kidney and heart in CKD state, and elucidate the significant role of intestinal microbiota in the gut-kidney-heart axis hypothesis for the pathophysiological mechanisms of these diseases, during which process mitochondria may serve as a potential therapeutic target. Dysregulation of this axis will lead to a vicious circle, contributing to CKD progression. Recent studies suggest novel therapies targeting gut microbiota in the gut-kidney-heart axis, including dietary intervention, probiotics, prebiotics, genetically engineered bacteria, fecal microbiota transplantation, bacterial metabolites modulation, antibiotics, conventional drugs and traditional Chinese medicine. Further, the identification of specific microbial communities and their corresponding pathophysiological metabolites and the illumination of the gut-kidney-heart axis may contribute to innovative basic research, clinical trials and therapeutic strategies against CKD progression and uremic complications in CKD patients.